Unveiling the pressure-induced properties and ambient thermoelectric behaviour of Co2YZ (Z = Si, Ge, Sn) heusler alloys - Dehimi, Nour ElHouda; Dehbaoui, Mourad; Meliani, Kawther; Djennane, Khaoula; Benaisti, Ilhem; Kemal, Ozdogan (IOP Publishing Ltd, 2025)
In this study, we present a comprehensive first-principles investigation of the pressure-dependent structural, elastic, thermodynamic, electronic, magnetic, and thermoelectric properties of Co2YZ Heusler alloys (Z = Si, Ge, Sn). Calculations were carried out using both the plane-wave pseudopotential method (CASTEP) and the full-potential linearized augmented plane wave method (WIEN2k), enabling cross-validation of results. The elastic analysis indicates that Co2YSn remains mechanically stable up to 100 GPa, whereas Co2YGe and Co2YSi lose stability beyond 96 GPa and 83 GPa, respectively. Electronic band structure calculations at ambient pressure reveal a half-metallic character for Co2YSi, while Co2YGe and Co2YSn exhibit metallic behaviour. The corresponding spin polarization at the Fermi level is 100% for Co2YSi, 95% for Co2YGe, and 86% for Co2YSn. The total magnetic moments follow the Slater-Pauling rule and decrease progressively under pressure. Thermoelectric properties computed using the BoltzTraP code highlight Co2YSi as a promising candidate for low-temperature waste heat recovery, with potential implications for energy efficiency and sustainable materials design.
Keywords: heusler compound; DFT; condensed matter; thermoelectricity; spintronics; thermodynamic; HALF-METALLIC PROPERTIES; FULL-HEUSLER; TEMPERATURE; PERFORMANCE; PRINCIPLES; BULK; AL; Physics